Assessing the Prevalence and Predictors of Short Birth Spacing and its Association with Pregnancy Outcomes in Pakistani Women - Nadia Munir, Fouzia Jan, Hanana Hameed, Arifa Inayat, Bakhtawar Baloch, Saira Hout (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Short birth spacing, with intervals less than 24 months between pregnancies, poses serious risks to maternal and neonatal health. This study explores its prevalence, key predictors, and associated pregnancy outcomes among Pakistani women. Methodology: A descriptive cross-sectional study was conducted on 100 multiparous women attending the obstetrics and gynecology departments of two tertiary care hospitals in Pakistan between January and June 2023. Data were collected using structured interviews and antenatal records. Birth spacing was categorized based on interpregnancy interval (short: <24 months; adequate: ≥24 months). Maternal demographics, socio-economic indicators, and reproductive histories were recorded. Adverse pregnancy outcomes preterm birth, low birth weight, anemia, and neonatal ICU admission were analyzed. Statistical analyses, including chi-square and logistic regression, were performed to determine predictors and associations (p < 0.05 considered significant). Results: Out of 100 women, 46% had short birth spacing. The most significant predictors included maternal age <30 years (p = 0.021), lack of formal education (p = 0.008), rural residence (p = 0.034), and non-use of contraceptives (p < 0.001). Short birth spacing was significantly associated with higher rates of preterm birth (37% vs 18%, p = 0.014), low birth weight (41% vs 20%, p = 0.007), maternal anemia (52% vs 27%, p = 0.005), and increased neonatal ICU admissions (30% vs 12%, p = 0.016). Conclusion: Short birth spacing is highly prevalent among Pakistani women and is strongly linked with adverse maternal and neonatal outcomes. Targeted educational interventions, improved access to contraceptives, and strengthened antenatal counseling are essential to mitigate these risks and promote optimal birth intervals. Keywords: Short birth spacing, interpregnancy interval, maternal outcomes, neonatal outcomes, predictors.